Participatory scenario formulation with Bangladesh Planning commission informs Five Year Plans and SDG integration. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
A close collaboration with the Bangladesh Planning commission has resulted in the successful use of future scenarios to formulate the government? central development plan ? the 7th 5 year plan. Based on this success, Planning Commission members and other members of governments requested a long-term collaboration to build institutional capacities for foresight in the Bangladesh government, which has continued to guide country-wide planning, particularly around SDG implementation and next generation 5 year planning.